Postnatal growth and function of the pre-acinar airways. Issue 3 (May 1972) - Hislop, Alison; Muir, D. C. F.; Jacobsen, M.; Simon, G.; Reid, Lynne
Abstract : The postnatal growth of the pre-acinar or conducting airways of the lung was examined by measuring the dimensions of selected axial pathways in lungs at different stages of development. The material included both formalin-fixed specimens and bronchograms. A method of comparing the relative sizes of each part of the pathways was developed which allowed for differences between the number of branches or generations measured in each specimen. The results indicate that the pre-acinar airways of the infant may be regarded as a miniature version of those in the adult and that this relationship persists during postnatal growth. Each individual branch grows in a symmetrical fashion both in length and in diameter and bears a constant relation to the whole. The physiological function of the conducting airways during growth was investigated using published data on the breathing pattern of infants. Particular attention was given to the conditions of airflow, to the warming and humidification of inhaled air, and to the filtration of airborne dust.